Community-identified key research questions for the future of UK afforested peatlands - R.J. Payne; W. Jessop (Mires and Peat, 2018)
Large areas of UK peatland were planted with non-native conifers in the twentieth century, changing many aspects of the ecosystem. As these plantations reach harvesting age there are important questions about what should be done with them next, with key options including restocking for continued forestry and restoration. Making decisions on the future of these sites is difficult and the underlying evidence base is often incomplete. In order to prioritise future evidence needs we conducted a two-phase consultation exercise to identify what a large body of stakeholders in science, policy and practice consider to be the most important outstanding research questions. The five most popular questions identified were: How does the greenhouse gas balance of peatland forestry differ between deep and shallow peat and compare to forestry on mineral soils?; How does the greenhouse gas budget of a peatland change with initial afforestation, restocking or restoration?; Is it possible to have trees on peat without loss of biodiversity and carbon storage?; What are the limits to the achievability of forest-to-bog restoration in terms of factors such as peat condition, depth and site extent?; and What is the financial value of natural capital in natural and afforested peatlands and how does this change with restoration? Notable subsidiary themes included flooding, biodiversity and compensatory planting. These questions form potential foci for future research and particularly emphasise the importance of understanding carbon cycling in afforested peatlands.